Urban spaces in temporal dynamics: a semiotic view - Tchertov, Leonid (Revista de Arquitectura, 2023)
The purpose of this paper is to consider, with the methods of spatial semiotics, the communicative potencies of urban spaces and their temporal changes. In semiotic terms, architecturally formed spaces can be described as sets of spatial texts formed and interpreted with the help of diverse spatial codes. The forms of buildings, their places, the borders between areas with distinct meanings, and other spatial features are considered in this perspective as the semiotic means of inter-subject communication. However, their meanings change in time, and this can be described in the semiotic conceptual paradigm as the re-semiotization of architecturally formed spaces —the change of semantics and syntactic constructions of their spatial texts in new pragmatic conditions—. Another architectural context appearing around the historical buildings in the course of time, as well as diachronic changes of spatial codes, participate in these modifications. Thus, a semiotic analysis of the syntax and semantics of architecturally formed texts provides a method for the study of communication trough architecture, not only in synchrony, but also in diachrony.